Experimental study on double pipe PCM floor heating system under different operation strategies. (January 2020) - Lu, Shilei; Xu, Bowen; Tang, Xiaolei
Abstract: Phase change material (PCM) can be integrated into floor heating system to store excess heat, releasing it when needed, thus effectively reducing the mismatch between energy supply and demand. In this study, a double pipe PCM floor heating system with three independent heating modules was proposed for clean energy heating in rural China. A 26-day experimental study was conducted to study the operation effect of the system under four different strategies. Strategy 1: partial power operation strategy; Strategy 2: daytime energy storage strategy; Strategy 3: nocturnal energy storage strategy; and Strategy 4: phased energy storage strategy. In the early stage of heating, the average temperature of experiment room was 18.9 °C and the daily temperature fluctuation was controlled within 2.1 °C, which showed an effective guarantee of indoor comfort under Strategy 1. In the late stage of heating, the differences in indoor temperature fluctuations could be caused by changes in outdoor climate and operation strategies. And operating strategy had less impact on indoor temperature distribution. Moreover, the experiment results revealed that the system could provide a comfortable indoor thermal environment while adjusting operational strategies. And the 3 °C average daily temperature fluctuation confirmed the feasibility of creating a comfortable environment with gentle temperature fluctuations via the PCM floor intermittent heating. Highlights: A double pipe PCM floor heating system with three independent modules was proposed. Operation effects of the system under four different strategies were investigated. Indoor temperature can be evenly distributed regardless of the adopted strategy. The system can ensure indoor thermal comfort while adjusting operation strategies. The average indoor daily temperature fluctuation was 1.8 °C; the minimum was 3.0 °C.